Perancangan Sistem Informasi Penjualan Dan Pengolahan Data Barang Pada CV Mutiara Abadi Menggunakan Metode Waterfall - Rivaldi; Faisal Sukma; Hendra Wibowo (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
CV Mutiara Abadi is a place that sells clothes in Legok. The system used at CV Mutiara Abadi is still very manual starting from data collection, transactions and reporting. Data collection of goods and transactions still uses handwriting so that recording errors often occur and it is difficult to find data due to accumulation of files. Therefore it is necessary to solve the problem to make it easier for staff to work, namely by making a program of transactions and stock of goods using the waterfall method, the process is structured and then tested with blackbox testing so as to produce an effective and efficient quality program. This program is expected to be able to support all sales and inventory data collection activities at CV Mutiara Abadi as a whole so that it can improve transaction services and inventory data collection and report generation.